2022
DOI: 10.1021/acs.biomac.1c01248
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Chitosans from Different Fungi with Special Emphasis on Zygomycetous Dimorphic Fungus Benjaminiella poitrasii: Evaluation of Its Chitosan Nanoparticles for the Inhibition of Human Pathogenic Fungi

Abstract: The cell wall chitosan was extracted from fungi belonging to different taxonomic classes, namely, Benjaminiella poitrasii (Zygomycetes, dimorphic), Hanseniaspora guilliermondii, Issatchenkia orientalis, Pichia membranifaciens, and Saccharomyces cerevisiae (Ascomycetes, yeasts), and Agaricus bisporus and Pleurotus sajor-caju (Basidiomycetes). The maximum yield of chitosan was 60.89 ± 2.30 mg/g of dry mycelial biomass of B. poitrasii. The degree of deacetylation (DDA) of chitosan extracted from different fungi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Figure (4) shows the physical properties of chitosan extracted from the stems of the A.bisporus brown, as the rate of Degree of deacetylation for chitosan under study was 83%, and this percentage is within the range mentioned by [40], which indicated that the degree of deacetylation of chitosan extracted from yeast and fungi, depending on the results of the FTIR, ranged between (79 -87)%, while the percentage of deacetylation based on the Nuclear Magnetic Resonance method was (89 -70)%. [24] showed when estimating Degree of deacetylation from chitosan extracted from mushrooms, which amounted to 78.1%, while [35] indicated that the percentage of Degree of deacetylation from chitosan produced from A.bisporus reached 66.35%.…”
Section: Physiochemical and Functional Properties Of Chitosanmentioning
confidence: 63%
“…Figure (4) shows the physical properties of chitosan extracted from the stems of the A.bisporus brown, as the rate of Degree of deacetylation for chitosan under study was 83%, and this percentage is within the range mentioned by [40], which indicated that the degree of deacetylation of chitosan extracted from yeast and fungi, depending on the results of the FTIR, ranged between (79 -87)%, while the percentage of deacetylation based on the Nuclear Magnetic Resonance method was (89 -70)%. [24] showed when estimating Degree of deacetylation from chitosan extracted from mushrooms, which amounted to 78.1%, while [35] indicated that the percentage of Degree of deacetylation from chitosan produced from A.bisporus reached 66.35%.…”
Section: Physiochemical and Functional Properties Of Chitosanmentioning
confidence: 63%
“…Astragalus membranaceus root extract Polysaccharide nanoparticles [8,9] Cellobiose Cryoprotectant for liposomes [10] Chia seed oil from Salvia hispanica L. Liposomes and nanoemulsions [11] Chitosan extracted from fungi (Aspergillus niger; Agaricus bisporus) Chitosan nanoparticles [8,12,13] Chondroitin sulphate (synthetic) Polysaccharide nanoparticles [14][15][16] Coagulated potato proteins Protein-based nanoparticles [17,18] Dextran from Leuconostoc mesenteroides Polysaccharide nanoparticles Reviewed by [19] Digitaria exilis Polysaccharide nanoparticles [20] Eggshell membrane protein hydrolysate Protein-based nanoparticles [21][22][23] Fucoidan extracted from the seaweed Fucus vesiculosus and Undaria pinnatifida Polysaccharide nanoparticles [24][25][26] Guar gum Polysaccharide nanoparticles [27] Lucerne leaf extract from Medicago sativa Protein-based nanoparticles [28] Mung bean seed proteins from Vigna radiata Protein-based nanoparticles [29,30] Panax notoginseng root extract Polysaccharide nanoparticles [31] Phytoglycogen Polysaccharide nanoparticles Polyelectrolyte complex [32][33][34][35][36][37] Phytosterols Solid lipid nanoparticles Liposomes [38,39] Phospholipids from egg yolk Liposomes [40][41][42] Phosphatidylserine from soya and fish phospholipids Liposomes [43,44] Rapeseed protein from Brassica nap...…”
Section: Material(s) From Novel Foods Type Of Carrier Referencesmentioning
confidence: 99%
“…The use of mushrooms as a source of chitosan is advantageous due to the homogeneity and highly deacetylated nature of the product [56]. Mane and co-workers examined fungal organisms in the waste fungal biomass of the wine and mushroom industries and the fermentation of the zygomycete fungus B. poitrasii [12]. In addition to the production and characterization of the extracted chitosan, the synthesis of fungal chitosan nanoparticles was also conducted to determine their antifungal potential against human pathogenic fungi.…”
Section: Material(s) From Novel Foods Type Of Carrier Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan is a natural polysaccharide, synthesized by deacetylation of chitin, extracted from marine or plant-based sources (crustaceans, insects, microorganisms, fungus, seaweed) [17][18][19][20]. This type of biopolymer is often used as a material support to immobilize enzymes.…”
Section: Introductionmentioning
confidence: 99%